The moderator role of innovative behaviors on the relationship between transformational leadership and organizational innovation - Mokhber, Mozhdeh (2013)
Leading innovation in today’s competitive business environment is one of the most challenging aspects of the life of an organization. Review of literature indicates that although innovation is accepted as a key factor to future competitiveness of the firms, in many developing countries but organizational innovation is not a priority and generally neglected. Since previous studies identified leadership as an important determinant of organizational innovation, this study seeks to explore the direct and moderated effect of transformational leadership on organizational innovation at the organizational level. Therefore, this study develops a conceptual framework to show the moderating effect of innovative behaviours (idea generating, risk taking, decision making) as an organizational context on the relationship of transformational leadership and organizational innovation. A sample of 63 companies from “Top 100 Iranian Companies” participated in this research. The hypotheses were evaluated using Partial Least Squares (PLS) analysis which is known as a Structural Equation Modeling (SEM) technique. Findings of this study revealed that almost 45 percent of the variance of organizational innovation (R2 = 0.449) is explained by transformational Leadership and this supported the positive and significant relationship of transformational leadership and organizational innovation. Furthermore, the results of this research supported two of the predicted moderating effects and showed that some of the components of transformational leadership are positively related to organizational innovation. This research has both theoretical and practical contributions to the field of leadership and innovation by elaborating the direct and moderated effect of transformational leadership on organizational innovation.